EFFECT OF ELASTIC WRAPPING OF LOWER LIMBS ON HEMODYNAMIC CHANGES AFTER SPINAL ANESTHESIA IN LOWER ABDOMINAL SURGERIES - Basant Kumar Pareek; Vinit Kumar Khemka; Kiran Bala; Siddhartha Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Spinal anesthesia is preferred for lower abdominal surgeries due to its benefits, but it can cause post-spinal hypotension (PSH). This study examines the effect of elastic wrapping of lower limbs on hemodynamic changes post-spinal anesthesia.Methods: This double-blinded, randomized control study involved 60 patients undergoing lower abdominal surgery under spinal anesthesia. Patients were divided into two groups: Group A (legs wrapped with crepe bandages) and Group B (no wrapping). Hemodynamic parameters were monitored, and the incidence of hypotension and tachycardia was recorded.Results: Group A exhibited significantly higher systolic and diastolic blood pressures at various intervals post-spinal anesthesia compared to Group B. The mean arterial pressure was also higher in Group A. The incidence of hypotension and tachycardia was significantly lower in Group A, with reduced need for rescue vasopressors.Conclusion: Elastic wrapping of the lower limbs significantly stabilizes hemodynamic parameters following spinal anesthesia, reducing the incidence of hypotension and tachycardia. This non-pharmacological method is simple, safe, and effective.